2015
DOI: 10.7314/apjcp.2014.15.24.10893
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of MGMT Promoter Methylation and TP53 Mutation in Glioblastomas Depends on IDH1 Mutation

Abstract: Asian Pac J Cancer Prev, 15 (24), 10893-10898 IntroductionGlioblastoma multiform (GBM), classified as World Health Organization (WHO) grade IV, is the most common malignant brain tumors in adults with an incidence rate of 23 per 100,000 persons (Stancheva et al., 2014). Their clinical course varies substantially, such that some patients succumb to progressive disease within weeks while others survive for a decade or more. Current treatments include surgery, radiation therapy and chemotherapy (Sathornsumetee et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…Survival analysis of the TCGA astrocytoma dataset confirmed our findings. In LGG, this is the first report of TP53 mutation being a favourable prognostic factor, although this was reported previously in other cancers, including glioblastoma [93,94], sarcomas [95], ovarian serous cystadenocarcinoma [96] and cervical cancer [97]. In multivariate analysis adjusting for IDH1 mutation, age, gender and tumour grade, the combined TP53 mutation showed a trend for improved survival compared to WT, leading us to believe there are specific TP53 mutations accounting for the improved survival in the univariate analysis.…”
Section: Discussionmentioning
confidence: 56%
“…Survival analysis of the TCGA astrocytoma dataset confirmed our findings. In LGG, this is the first report of TP53 mutation being a favourable prognostic factor, although this was reported previously in other cancers, including glioblastoma [93,94], sarcomas [95], ovarian serous cystadenocarcinoma [96] and cervical cancer [97]. In multivariate analysis adjusting for IDH1 mutation, age, gender and tumour grade, the combined TP53 mutation showed a trend for improved survival compared to WT, leading us to believe there are specific TP53 mutations accounting for the improved survival in the univariate analysis.…”
Section: Discussionmentioning
confidence: 56%
“…The expressions of MGMT RNA and protein are decreased by methylation of a CpG island in its promoter region [7,8]. Thus, aberrant hypermethylation of the MGMT promoter region (hmMGMT) may hamper its DNA repair function, allowing mutations of G:C>A:T transition in TP53, as well as other carcinogenic genes, in various cancers [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…1 C). Recently, it was reported that TP53 mutation status alone is associated with improved survival in glioblastoma 27 . Our results support this observation.…”
Section: Discussionmentioning
confidence: 99%